INTELLECTUAL WELLNESS: A CRITICAL COMPETENCY FOR MANAGING TRANSFORMATION AND CHALLENGES IN SOUTH AFRICAN HIGHER EDUCATION INSTITUTIONS - Botha, Petrus Albertus (South African Journal of Higher Education, 2016)
The complex challenges occasioned by transformation and other changes in higher education in South Africa impose significant intellectual demands on managers. This paper reports the results of an investigation into the intellectual wellness levels of managers at two South African universities. The purpose of the study was to determine whether managers at higher education institutions in South Africa engage in activities and behaviour that stimulate intellectual development and growth. A survey was conducted among 324 managers at both universities by means of a questionnaire. The study was carried out within the qualitative paradigm, and descriptive and inferential statistical procedures were used to analyse the quantitative data. The Cronbach’s alpha of 0.82 showed that the instrument used was reliable for measuring the intellectual wellness behaviour levels of managers. T-tests were conducted to compare the mean scores of four selected managerial groups, while an ANOVA was used to compare the mean scores of three managerial age groups. The combined average score of 84.38% suggested that the managers had high levels of intellectual wellness. A minority number of respondents obtained scores less than 60%, which indicate the need for intellectual wellness development interventions. These managers should engage in specific activities to stimulate their intellectual development and growth, such as keeping themselves informed about social and political issues; learning about scientific discoveries; seeking opportunities to acquire new competencies and skills (for example, written and verbal, and computer and interpersonal skills) and improving their academic qualifications.